2009
DOI: 10.1038/ja.2009.46
|View full text |Cite
|
Sign up to set email alerts
|

An alternative menaquinone biosynthetic pathway operating in microorganisms: an attractive target for drug discovery to pathogenic Helicobacter and Chlamydia strains

Abstract: Menaquinone is an essential vitamin as an obligatory component of the electron transfer pathway in microorganisms. Menaquinone has been shown to be derived from chorismate by eight enzymes, designated MenA to -H in Escherichia coli. However, bioinformatic analyses of whole-genome sequences have suggested that some microorganisms, such as Helicobacter pylori and Campylobacter jejuni, which are known to cause gastric carcinoma and diarrhea, respectively, do not have orthologs of most of the men genes, although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
56
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 27 publications
2
56
0
Order By: Relevance
“…In 2005, it was reported that various Streptomyces species lack orthologs of the menB--menF genes (12), suggesting that an entirely unique biosynthetic pathway is operative in these organisms. Interestingly, these genes are also absent in the pathogenic bacteria C. jejuni and H. pylori, even though these organisms are known to biosynthesize menaquinone (9). Isotopic feeding studies confirmed that a unique pathway is employed in Streptomyces, and 1,4-dihydroxy-6-naphthoate (DHN) was implicated as an intermediate (see Fig.…”
mentioning
confidence: 69%
See 3 more Smart Citations
“…In 2005, it was reported that various Streptomyces species lack orthologs of the menB--menF genes (12), suggesting that an entirely unique biosynthetic pathway is operative in these organisms. Interestingly, these genes are also absent in the pathogenic bacteria C. jejuni and H. pylori, even though these organisms are known to biosynthesize menaquinone (9). Isotopic feeding studies confirmed that a unique pathway is employed in Streptomyces, and 1,4-dihydroxy-6-naphthoate (DHN) was implicated as an intermediate (see Fig.…”
mentioning
confidence: 69%
“…Bioinformatic analysis strongly implied that the futalosine pathway is also operative in the pathogenic organisms C. jejuni and H. pylori (9,14). These bacteria lack homologs to the men genes of E. coli and possess homologs to the mqn genes of S. coelicolor.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…E. coli) utilize the traditional route. The absence of futalosine genes in these organisms strengthens the development of antimicrobial compounds targeting pathogenic bacteria that synthesize MK (8).…”
mentioning
confidence: 99%